Dietary Quality and Caloric Contribution of the Alternative Food Acquisitions of U.S. Low-income Households: Results from the National Food Acquisition and Purchasing Survey (Foodaps). Issue 5 (3rd September 2022) - Crespo-Bellido, Mayra; Takata, Yumie; Jackson, Jennifer; Grutzmacher, Stephanie; Smit, Ellen
ABSTRACT: Low-income households may acquire foods from purchases, federal food assistance, and alternative food sources (AFS) to meet their food needs. The objectives of this study were to quantify and compare the contribution of AFS to total kilocalories and dietary quality of food acquisitions between AFS users and non-users among low-income households. Users obtained 22.3% of kilocalories from AFS and purchased fewer kilocalories compared to non-users [14, 886 ± 1464.10 versus 19, 915.00 ± 1036.41 kilocalories]. AFS users had lower 2015-Healthy Eating Index scores from purchased acquisitions than non-users, but there was no difference in dietary quality between AFS users and non-users after accounting for alternative acquisitions.